Survival prediction using the Freiburg index of post-TIPS survival (FIPS) in critically ill patients with acute- on chronic liver failure: A retrospective observational study - Luxenburger, Hendrik; Schmidt, Katharina; Biever, Paul; Supady, Alexander; Sekandarzad, Asieb; Roehlen, Natascha; Reincke, Marlene; Neumann-Haefelin, Christoph; Schultheiss, Michael; Wengenmayer, Tobias; Thimme, Robert; Bettinger, Dominik (Frontiers in Medicine, 2022)
Background and aim Liver cirrhosis in patients treated in the intensive care unit (ICU) is associated with high mortality. Well established scores are useful to allow for assessment of prognosis and support ICU treatment guidance. However, currently used scoring systems often do not reflect the complexity of critically ill patients. Therefore, we tested the newly developed Freiburg index-of post-TIPS survival (FIPS) score in order to assess its potential role for prognostication of cirrhotic patients in the ICU. Methods A total of 310 patients with liver cirrhosis treated in the ICU between 2010 and 2021 were enrolled in this retrospective observational study. Prognostic factors for mortality and 28-day mortality were assessed. Moreover, using c indices the prognostic discrimination of different prognostic scores was analyzed. Results The FIPS score allowed to discriminate patients with high ICU mortality and within 28-days after ICU treatment (ICU mortality: 42.2 vs. 59.9%, p = 0.008 and 28-day mortality: 43.3 vs. 74.1%, p < 0.001). However, the FIPS score in its current composition showed no superior prognostic discrimination compared to other established scores. Multivariable analyses identified the FIPS score (HR 1.25 [1.04–1.49], p = 0.015) and lactate at admission (HR 1.07 [1.04–1.09], p < 0.001) as significant predictors of ICU mortality. Lactate at admission substantially improved patient risk stratification within each FIPS risk groups. Conclusion Similar to other commonly used scores, the FIPS score in its current composition does not allow a sufficiently reliable prognostication of critically ill patients treated in the ICU. However, adding lactate as additional factor to the FIPS score may improve its prognostic ability.